Effects of the Recipient Strain and Ultraviolet Irradiation on Transduction Kinetics of the Penicillinase Plasmid of Staphylococcus aureus - Rubin, Sally J. (1971)
When the penicillinase plasmid of Staphylococcus aureus PS 81(P(81))(T(81)) was transferred to its cured derivative of PS 81(N(P))(T(81)), there was a fivefold increase in the transduction frequency of penicillinase plasmid markers after ultraviolet (UV) irradiation of the phage instead of the expected decrease typical for plasmid-borne markers. These results were independent of the transducing phage, the donor, and the method of curing the recipient and were also obtained with a cured derivative of PS 80(PI(80)). With PS 52, a naturally occurring penicillin-sensitive strain, and a cured transductant of PS 52 as the recipients, typical plasmid kinetics were observed. The plasmid location of penicillinase plasmid markers in transductants was confirmed by their instability in ethidium bromide (EB). In a cross between isogenic plasmids (PI(258)penZ cad × PI(258)penI asa ero), transductants were doubly selected for cadmium and erythromycin resistances. There was a twofold increase in transduction frequency after UV irradiation of the transducing phage and an increase in the proportion of recombinant type transductants. CsCl-EB density centrifugation revealed that plasmid deoxyribonucleic acid (DNA) was present in PS 81(P(81))(N(T)) and its cured derivative [PS 81(N(P))(N(T))], but not in PS 52. Sucrose gradient analysis of plasmid DNA showed that the penicillinase plasmid of PS 81(P(81))(N(T)) was larger than the plasmid in its cured derivative. Thus, the cured derivative contains plasmid DNA which appears to recombine with the incoming plasmid, causing the rise in transduction frequency noted after UV irradiation of transducing phage.